ANALISIS DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI TANAMAN PANGAN PADA LAHAN KERING DAN RANCANG BANGUN SISTEM INFORMASINYA - Apriana, Yayan; Susanti, Erni; Suciantini, nFn; Ramadhani, Fadhlullah; Surmaini, Elza (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Changes in the frequency and severity of extreme climate events and in the variability of weather patterns will have significant consequences for stability of agricultural system. Research objectives were to a) analyze the Impact of Climate Change on Food Crops in Dryland b) develop a software prototype analysis of the impact of climate change on food production, especially upland rice and maize on dry land; c) create a simulation with multiple scenarios of the impact of climate change on dry land. The study was conducted in South Sulawesi, West Nusatenggara and East Nusatenggara.The activities were carried out by projecting precipitation using scenarios: a) SRESA2 (Scenarios of climate change by assuming economic growth is lower and population growth remains high so the rate of greenhouse gas emissions increased, b) SRESB1 (scenario of climate change by assuming mitigation efforts through expanding efficient use of energy and technology improvements so that the emission levels are lower) and making projections of production of upland rice and maize using Decission Support System for Agrotechnology Transfer (DSSAT) as resource information in the preparation of prototype software information Systems Climate Change Impacts on Crop Production (SIDaPi TaPa). The system was built based on the analysis simulation model projections of production output DSSAT. Based on SRES scenarios A2, the decline in rainfall increased until 2050 in several districts, in South Sulawesi, West Nusatenggara and East Nusatenggara.Treatment of adaptation through SRESB1 scenarios could be effective to anticipate a decrease in rainfall in some regions, either in 2025 or 2050. In general, the region experiencing a decrease in rainfall will also decrease in production of both upland rice and maize production. The decline in upland rice production by SRESA2 scenario until 2050 was between 20-25%, and by a scenario adaptation SRESB1 the decline in production could be minimized to only between 7 -10%.The decline in maize production in the plot until 2050 by SRESA2 was between 9-15%, using scenarios to reduce production SRESB1 was only 5-8%. SIDAPI TAPA is a software analysis of the impact of climate change on food production, especially upland rice and maize on dry land in South Sulawesi, West Nusatenggara and East Nusatenggara.